SCHOOL FAILURE COROLLARY TO SOCIAL DROP-OUT BY POOR CHILDREN (Annual of the Faculty of Philosophy in Skopje, 2008)
In this paper we analyze the influence of school failure on social drop- out of poor children with a special stress on the problems and consequences of repeating the grades, dropout rate, and non comprised knowledge or skills for successful integration in the professional world. Social withdrawal corollary with school failure and comprise loneliness and depression. Furthermore, the fillings of insurance and/or social inhibition leads less inclusion in the real world and to school failure too. Therefore, child and young man can less improve skills for solving impersonal and interpersonal problems. Behavioral inhibition was challenged by interaction of biological, social factors and negative self esteem, which loneliness is result.By means of studying we want to show that reducing school failure specially for poor young people cannot be just one school ’s problem; the initiative has to came from the state, namely from the different sectors, not just educational, like health insurance, social security\ employment. The responsibility for academic achievement has to be shared by individual students, school, state public institutions and services as well as research organizations. The role of counseling service in reducing school failure is important too. There activities have to be interrelated[
Keywords: SCHOOL FAILURE; SOCIAL DROP-OUT; WITHDRAWAL; POOR CHILDREN